Constitutional Ijtihad and the Reform of Islamic Family Law: A Comparative Analysis of Indonesia and Egypt in Advancing SDG 16 - Fuad Riyadi; Ahmad Remanda; Abdurrohman Kasdi; Arif Marsal (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the role of constitutional ijtihad in transforming Islamic family law in Indonesia and Egypt within the framework of national legislation, focusing on its contribution to the achievement of Sustainable Development Goal (SDG) 16, which promotes peace, justice, and strong institutions. Theoretical framework: The theoretical framework of this research is based on the concept of constitutional ijtihad that integrates Islamic norms with contemporary social standards and human rights, as well as comparative legal theory as an analytical instrument in the development of a just and inclusive legal system. Literature review: The literature review includes a review of Islamic family law reforms in Indonesia and Egypt which include aspects such as the determination of the minimum age of marriage, the obligation to register marriage, the regulation of polygamy, the unilateral restriction of ṭalāq by the husband, the recognition of khuluʿ as a form of divorce by the wife, the legal status of children born during the ʿiddah period, and the renewal of inheritance law through the application of the concept of waṣiyyah wājibah. Methods: This study uses a comparative legal approach to identify similarities and differences in Islamic family law reform in the two countries, taking into account the framework of legal traditions, political contexts, and various interpretations of applicable fiqh. Results: The results show that both Indonesia and Egypt have made progressive adjustments to Islamic family law to improve legal certainty, gender equality, and social justice, albeit through different legal traditions, political dynamics, and sharia interpretations. Implications: The legal transformation in both countries demonstrates a targeted strategy to build an inclusive and equitable legal system, in line with SDG 16, and has the potential to become a model for Muslim-majority countries. Novelty: Presents a comparative analysis of the application of constitutional ijtihad in Islamic family law reform in two countries with different legal and political traditions, which are directly linked to the achievement of SDG 16.